Technical Note—Demand Uncertainty Reduction in Decentralized Supply Chains. Issue 1 (21st October 2016) - Li, Meng; Petruzzi, Nicholas C.
Abstract : This note analyzes the effects associated with reducing demand uncertainty in a decentralized supply chain comprising one manufacturer, one retailer, and a wholesale price contract that governs the transactions between them. The demand uncertainty level is parameterized through a mean‐preserving spread, and the manufacturer's and the retailer's equilibrium decisions are solved accordingly. We consider the case of an exogenous retail price as well as the case of an endogenous retail price, and we find in both cases that the manufacturer's and the retailer's expected profits in equilibrium are not necessarily monotone decreasing in the uncertainty level. Thus, we find that, even if the cost of reducing demand uncertainty is zero, uncertainty reduction can hurt rather than benefit either or both members of the supply chain.